Respuesta :

Answer:

J. 6a^3b^8

Step-by-step explanation:

(-2ab^3)(-3a^2b^5)

-2a x -3a^2 = 6a^3...

b^3 x b^5 = b^8...

6a^3b^8

Answer:

J)  [tex]6a^{3} b^{8}[/tex]

Step-by-step explanation:

So basically all you have to do is multiply the coefficient first

so

(-2)(-3) = 6

after you find your coefficient start with the variables all you have to do is add the exponents so

a + [tex]a^{2}[/tex] = [tex]a^{3}[/tex]

[tex]b^{3}[/tex] + [tex]b^{5}[/tex] = [tex]b^{8}[/tex]

That's it [tex]6a^{3}b^{8}[/tex]

Hope this helps :)